Application of Minimally Invasive Oral Swab Samples for qPCR-Based Sexing in Neognathae Birds - Maria-Carmen Turcu; Anamaria Ioana Paștiu; Lucia-Victoria Bel; Anca-Alexandra Doboși; Dana Liana Pusta (Veterinary Sciences)
Birds are inherently social creatures that rely on pairing to enhance their well-being. Since many bird species lack obvious physical differences between females and males, sex identification is essential for ensuring their welfare. Additionally, early determination of the sexes of birds is crucial for their breeders, especially considering that most companion birds do not display clear sexual characteristics. Molecular genetic sexing has been demonstrated to be the most reliable method for determining the sexes of monomorphic birds. The objective of the present study was to demonstrate rapid, effective, and precise identification of sex in birds through quantitative real-time PCR (qPCR) using samples obtained via a minimally invasive technique (oral swabs). This qPCR method assesses variations in gene copy numbers within conserved Z-specific genes such as CHRNA6, DDX4, VPS13A, LPAR1, and TMEM161B, which are absent from the W chromosome. A total of 34 samples were included in this study from the following 17 bird species: domestic pigeon (Columba livia domestica), domestic chicken (Gallus gallus domesticus), domestic goose (Anser anser f domesticus), domestic duck (Anas platyrhynchos domesticus), Mute swan (Cygnus olor), Budgerigar (Melopsittacus undulatus), Lovebird (Agapornis roseicollis), Cockatiel (Nymphicus hollandicus), Red-rumped parrot (Psephotus haematonotus), Rose-ringed parakeet (Psittacula krameri), African grey parrot (Psittacus erithacus), domestic Canary (Serinus canaria forma domestica), Goldfinch (Carduelis carduelis major), Gouldian Finch (Chloebia gouldiae), Red Siskin (Carduelis cucullata), Australian Zebra Finch (Taeniopygia castanotis), and Common buzzard (Buteo buteo). The results proved that the CHRNA6, DDX4, VPS13A, LPAR1, and TMEM161B genes can reveal the sexes in the Neognath birds tested.